Correlation between dentofacial esthetics and mental temperament: A clinical photographic analysis using visagism - Tanikonda Rambabu; Chava Gayatri; Girija S Sajjan; P Venkata Karteek Varma; Visinigiri Srikanth (Wolters Kluwer Medknow Publications, 2018)
Background: "Visagism," a proposed novel concept, makes it possible for the patients to express the desirable emotions and personality traits, through their smile. According to this concept, clinicians can design a smile that blends with the patient's physical appearance, personality, and desires. Aim: To establish a relation, if any, between the smile pattern (dentofacial esthetics determined by three parameters, i.e., tooth form, long axes of maxillary anterior teeth, and connection line between embrasure) and the personality traits (four mental temperaments) through the concept of visagism. Settings and Design: A total of 190 participants aged between 20 and 38 years from a dental college were selected for the study. Materials and Methods: The temperaments of the participants were identified using a self-reporting questionnaire. The photographs of frontal view of teeth in centric occlusion of the participants were captured, and their tooth forms, long axes, and embrasure lines were drawn using photograph editing software. The type of temperament obtained from the questionnaire for each participant was compared with that obtained from photographic evaluation. Statistical Analysis Used: The obtained data were statistically analyzed by applying Kappa statistics for kappa measure of agreement. Results: There was no agreement between temperaments derived through questionnaire and those temperaments obtained from the photographic analysis. Conclusion: Although the concept of combining the principles of smile design and mental temperaments through visagism is an appreciable idea, it lacks a practical approach to create a personalized smile for each patient by including mental temperaments at present stage.